Evaluation of cementing results for high pressure, high temperature wells in Nam Con Son basin - Pham Truong Giang; Le Vu Quan; Nguyen Minh Quy; Le Thi Thu Huong; Do Van Hien; Truong Hoai Nam (Petrovietnam Journal, 2014)
This article summarises the results of the cementing process for high pressure, high temperature (HPHT) wells in the Nam Con Son basin, for the purpose of evaluating the success rate, geological and operation challenges and lessons learnt in order to propose solutions and techniques to improve the quality of future drilling and cementing for high pressure, high temperature wells in the Nam Con Son basin.